1984
DOI: 10.1139/p84-136
|View full text |Cite
|
Sign up to set email alerts
|

Cross relaxation at the lysozyme–water interface: an NMR line-shape-relaxation correlation study

Abstract: In wet hen egg white lysozyme (HEWL), the molecular dynamics at the lysozyme–water interface was studied using a proton NMR line-shape-relaxation correlation approach that employed selective inversion of the proton magnetization. The intrinsic lysozyme proton spin-lattice relaxation rate, the intrinsic water proton spin-lattice relaxation rate, and the lysozyme proton – water proton cross-relaxation rate were determined. The lysozyme proton – water proton intermolecular interaction couples these protons and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…4). The observation of such a negative reconstructed FID, with associated T 1 shorter than the minimum T 1 found in the T 1 HH results (Table 2), provided strong evidence for magnetization exchange between a solid‐like and a liquid‐like spin reservoir (16, 25). In our cartilage samples exchange was detected between the S and L2 spin reservoirs which proceeded at a relativity high rate.…”
Section: Resultssupporting
confidence: 91%
“…4). The observation of such a negative reconstructed FID, with associated T 1 shorter than the minimum T 1 found in the T 1 HH results (Table 2), provided strong evidence for magnetization exchange between a solid‐like and a liquid‐like spin reservoir (16, 25). In our cartilage samples exchange was detected between the S and L2 spin reservoirs which proceeded at a relativity high rate.…”
Section: Resultssupporting
confidence: 91%
“…8 for k with the parameters found for the anisotropic motion model (legend to Fig. 2) and the above 01 and r, we calculate k = 44 s-' at 40 MHz and 293 K. In a two-dimensional NMR time evolution study of proton magnetization in wet HEWL at the same frequency and temperature, a value for k = (98 ± 16) s-1 was deduced (22). Although the two values of k differ by a factor of -2, the results are nevertheless encouraging.…”
Section: Resultsmentioning
confidence: 91%
“…However, it must be kept in mind that such predicted rates are to be compared with the intrinsic water proton rates Rlwi and R2wi rather than the observed relaxation rates. In a recent study of cross-relaxation effects in wet HEWL at 40 MHz (22), it was shown that at room temperature the water-HEWL cross-relaxation rate had a value of -100 s'-i. This is approximately one-sixth of the observed proton rate R2W but >10 times as large as the observed rate R,W (8).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the observed water proton rates cannot be used directly to deduce dynamical information about the water molecules in protein solutions with absolute confidence due to possible contributions from water proton -protein proton intermolecular coupling that may produce spin-lattice relaxation and/or magnetization exchange effects [40][41][42]. In addition, exchange of labile protein hydrogens may play an important role [29].…”
Section: T1 Dispersionmentioning
confidence: 99%